2017
DOI: 10.15406/mojap.2017.03.00091
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Sexual Dimorphism from the Area of the Triangle

Abstract: Abbreviations: N, nasion; RIOF, right infraorbital foramen;LIOF, left infraorbital foramen; DRIOF, distance from the right infraorbital foramen to the nasion; DLIOFN, distance from the left infraorbital foramen to the nasion; DIOF, distance between the infraorbital foramina; PIOFN, perimeter formed by lines between the infraorbital foramina and the nasion; ATIOFN, area of the triangle formed by lines between the infraorbital foramina and the nasion IntroductionThe human skull is considered to be the second mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In both studies, the nasion was used as a reference point in order to establish and compare results between the sexes. In this study, the findings are greater in male than female [13,14]. These studies help to make comparisons between the radiological findings of these study with the findings of present study [14,15].…”
Section: Sah Et Al Conducted a Study On One Hundred Participants Of Y...supporting
confidence: 61%
See 1 more Smart Citation
“…In both studies, the nasion was used as a reference point in order to establish and compare results between the sexes. In this study, the findings are greater in male than female [13,14]. These studies help to make comparisons between the radiological findings of these study with the findings of present study [14,15].…”
Section: Sah Et Al Conducted a Study On One Hundred Participants Of Y...supporting
confidence: 61%
“…These studies help to make comparisons between the radiological findings of these study with the findings of present study [14,15]. Above mentioned articles [4][5][6][7][8][9][10][11]13] can be used to make a comparison between the radiological findings of them with the present research.…”
Section: Sah Et Al Conducted a Study On One Hundred Participants Of Y...mentioning
confidence: 89%
“…In relation to sex, the authors noted that there were statistically significant differences in the measurements of DIOF, DRIOFN, DLIOFN and the perimeter and area of the triangle delimited by the infraorbital foramina and the nasion and a multivariate difference in measurements. Thus a sexual dimorphism occurred in all measures and area that formed the triangle between the infraorbital foramen and the nasion that were larger in males [43].…”
Section: Role Of Osteologymentioning
confidence: 94%
“…Among all FM variables, the Length of Right Occipital Condyle (LRC), Minimum Intercondylar Distance (MnID), and Width of the Foramen Magnum (WFM) could determine sex using specific equation with an accuracy rate of 83% [37]. In a study to determine sexual dimorphism in Brazilian skulls from measurements of the area of the triangle formed between lines joining the IOFs to the nasion, 242 human skulls belonging to the Study and Research Center for Anatomy and Forensic Anthropology of Tiradentes University were used [43]. Observation showed that out of the 242 skulls examined, 148 were male and 94 were female, with ages ranging from 18 to 91 years.…”
Section: Role Of Osteologymentioning
confidence: 99%